ANALISIS PENYELESAIAN SENGKETA WARIS PERPEKTIF HUKUM ISLAM DAN HUKUM PERDATA DI INDONESIA - Suherman, Suherman; Adnan, Idul (Al-Muqaronah: Jurnal Perbandingan Madzhab dan Hukum, 2024)
This research aims to analyze the resolution of inheritance disputes from the perspective of Islamic law and civil law in Indonesia. Islamic inheritance law, which is based on the Al-Quran and Sunnah, provides clear guidelines for the distribution of inherited assets with the principles of justice and legal certainty. Meanwhile, civil law regulated in the Civil Code (KUHPerdata) offers flexibility and freedom in managing inheritance through wills and agreements between heirs. The research method used is descriptive-analytical with a qualitative approach, examining statutory regulations, court decisions and related literature. The research results show that although there are fundamental differences in the approaches of these two legal systems, they both have the same goals, namely achieving fair distribution of inheritance and effective dispute resolution. Religious courts and district courts as institutions with authority to resolve inheritance disputes, each have different but complementary mechanisms and procedures. This research suggests the importance of harmonization between Islamic law and civil law in resolving inheritance disputes in Indonesia, as well as strengthening mediation and arbitration mechanisms to reduce conflicts and reach fair agreements for all parties involved.